Biodegradation of phenol by cold-adapted bacteria from Antarctic soils - Lee, Gillian Li Yin; Ahmad, Siti Aqlima; Yasid, Nur Adeela; Zulkharnain, Azham; Convey, Peter; Wan Johari, Wan Lutfi; Alias, Siti Aisyah; Gonzalez-Rocha, Gerardo; Shukor, Mohd Yunus (Polar biology, 2018)
Phenol is an important pollutant widely discharged as a component of hydrocarbon fuels, but its degradation in cold regions is a great challenge due to the harsh environmental conditions. To date, there is little information available concerning the biodegradation of phenol by indigenous Antarctic bacteria. This study addresses the isolation of three phenol-degrading bacterial strains from King George Island, Antarctica. Based on preliminary screening, three isolates (AQ5-05, AQ5-06 and AQ5-07) capable of completely degrading 0.5 g/L phenol within 120 h at 10 °C were selected for detailed study. Two were identified as Arthrobacter spp., and one Rhodococcus sp., based on 16S rRNA sequences. All strains were non-motile, Gram positive, oxidase negative and catalase positive. A study on the effects of parameters including temperature, pH, salinity and nitrogen source was conducted to optimise the conditions for phenol degradation. This revealed that the three isolates were psychrotolerant with the optimum temperature for phenol degradation between 10 and 15 °C. This study suggests the potential use of cold-adapted bacteria in the bioremediation of phenol over a wide range of low temperatures.